THE EFFECT OF AGRIBUSINESS SYSTEM IMPLEMENTATION TO DAIRY CATTLE FARMS PRODUCTIVITY IN SEMARANG REGENCY - Edy Prasetyo; Titik Ekowati; Dian Wahyu Harjanti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
The purposes of study were to examine the agribusiness system implementation of the dairy cattle farms; the average productions of dairy cattle and to analyse the effect of agribusiness system implementation on dairy cattle farm productivity. The study used survey methods and as elementary units were the dairy cattle farmers. The sample was determined by the Purposive quota sampling method towards 69 dairy cattle farmers. Data collected were primary and secondary data. Data were analysed using qualitative descriptive, quantitative descriptive, and inferencial statistic methods (multiple linear regression). The result showed that: (i) the agribusiness implementation system was in good category with score 3.97; (ii) the average business scale of dairy cattle farms was 3.74 head/farmer with composition of lactation dairy cattle and non-lactation dairy cattle was 42.25% and 57.75% respectively, and the milk productivity was 9.05 lt/head/day; (iii) Simultaneously, agribusiness subsystem was significant influenced to cow's milk productivity, while in partial term, the preproduction subsystem, agribusiness support access subsystem, and agribusiness planning were a significant effect on the productivity of dairy cattle farms, while the livestock business management subsystem was no significant effect.